Use of Botanicals for the Management of Pulse Beetle (Callosobruchus maculatus F.) in Lentil - Paneru, Ram B; Shivakoti, Gopal P (Nepal Agriculture Research Journal, 2011)
Some plant materials, sweet flag (Acorus calamus), goat weed (Ageratum conyzoids), lantana (Lantana camara), Indian privet (Vitex negundo), mug-wort (Artimisia vulgaris), chinaberry (Melia azederach), rice husk ash, mustard (Brassica spp.) oil and neem (Azadirechta indica) oil were evaluated for their effects against pulse beetle (Callosobruchus maculatus F.). The powder or oil from the above plant materials were thoroughly admixed at the rate of 0.5, 1 and 2% w/w or v/w with lentil grains. Randomly selected 25 pulse beetle adults were exposed to the grains for each concentration of the main treatment. Rhizome powder of sweet flag, rice husk ash and mustard oil showed a significant effect in killing the pulse beetle within a week at 0.5, 1 and 2% concentrations. Neem oil was found very effective with 100% mortality of the beetle within two days. Other tested materials also showed insect killing properties but the effect was comparatively lower than that of sweet flag rhizome powder, mustard oil, neem oil and rice husk ash. Key words: Botanicals; Callosobruchus maculates; Lentil; Pulse beetle DOI: http://dx.doi.org/10.3126/narj.v4i0.4860 Nepal Agriculture Research Journal Vol. 4&5, 2001/2002 Page: 27-30 Uploaded date: 8 June, 2011